The epiphyseal scar joint line distance and age are important factors in determining the optimal screw length for medial malleoli fractures. Issue 4 (April 2019) - Çabuk, H.; İmren, Y.; Dedeoğlu, S.S.; Kır, M.Ç.; Gürbüz, S.; Gürbüz, H.
Highlights: The screw length should be decrease as the age increase in malleoli fractures. The epiphyseal scar joint line distance can be used to determine optimal screw length. If the surgeon is operating a patient over 60 years old, a 40 mm screw is optimal for medial malleoli fractures. Abstract: Aim: The screw length is important to achieve a stable fixation for medial malleoli fractures. We aimed to evaluate the optimal screw length for different age groups in surgically treated medial malleoli fractures. The second aim was to identify the utility of the distance of epiphyseal scar to joint line or joint line to medullary space for assessment of screw length. Material method: 368 X-rays and computed tomography (CT) images of ankle joints were retrospectively evaluated for optimal screw length, epiphyseal scar to joint line distance, joint to medullary space distance. The mean screw length for each decade was calculated. The correlations of screw length with age, screw length with distance of epiphyseal scar to joint line, and screw length with distance of joint line to medullary space were evaluated. Results: The optimal screw length was obviously decreased in patients in 61–70 and >70 years old group (p = 0.002). As the distance of epiphyseal scar from joint line was increased, the optimal length of screw was also increased (p = 0.001). The distance of epiphyseal scar from joint line was decreased by age (p = 0.011). Conclusion: The optimal screw length was decreased by age and the epiphyseal scar to joint line distance could be a clue for optimal screw length in medial malleoli fractures.